2016
DOI: 10.4028/www.scientific.net/kem.674.103
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Flame Cut Heavy Steel – The Residual Stress Profiling of Heat Affected Surface Layer

Abstract: Flame cutting is commonly used thermal cutting method in metal industry when processing thick steel plates. Cutting is performed with controlled flame and oxygen jet, which burns steel and forms cutting edge. Flame cutting process is based on controlled chemical reaction between steel and oxygen at elevated temperature. Flame cutting of thick wear-resistant steels is challenging while it can result in cracks on and under the cut edge. Flame cutting causes uneven temperature distribution in the plate, which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…It was also noted that a slower cutting speed and flame cutting with preheating produce a lower residual stress state in the cut edge. Similar results were obtained in other studies [13,14] by the author; the residual stress formation during flame cutting can be affected by the size of the sample and cutting parameters. In addition, preheating not only decreases the residual stresses in general but also increases the compressive stress region close to the surface by shifting the tensile stress region deeper into the subsurface.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…It was also noted that a slower cutting speed and flame cutting with preheating produce a lower residual stress state in the cut edge. Similar results were obtained in other studies [13,14] by the author; the residual stress formation during flame cutting can be affected by the size of the sample and cutting parameters. In addition, preheating not only decreases the residual stresses in general but also increases the compressive stress region close to the surface by shifting the tensile stress region deeper into the subsurface.…”
Section: Introductionsupporting
confidence: 89%
“…This study is a continuation for previous studies by the current author. The first study [14] confirmed that the residual state of the flame cut edge can be affected by variating the cutting parameters. In another study, [13] a model was developed to investigate the flame cut process and residual stress formation.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…[8] Transformation stresses arise from different microstructural transformations, which are accompanied by volume changes. [8] Previous studies [6,7,[9][10][11] have shown that flame cutting causes both residual compressive stress and high-tensile stress in the cut edge of the steel plate. The compressive stress is produced in the martensite region close to the cut edge and it is followed by high-tensile stress region in the tempered region.…”
Section: Introductionmentioning
confidence: 99%
“…The compressive stress is produced in the martensite region close to the cut edge and it is followed by high-tensile stress region in the tempered region. [7] The magnitude of the stresses and the width of these regions can be affected by the flame cutting parameters, [9,10] grain structure, [7] and the thickness of the plate. [6] In the worst case, flame cutting causes cracking of the cut edge.…”
Section: Introductionmentioning
confidence: 99%